Design of concurrent test Hardware for Linear analog circuits with constrained hardware overhead. - Ozev, S. (IEEE Transactions on VLSI systems)
Concurrent detection of failures in analog circuits is becoming increasingly more important as safety-critical systems become more widespread. A methodology for automatic design of concurrent failure detection circuitry for linear analog systems is discussed in this paper. The desired hardware bound is specified as a constraint; the methodology aims at providing coverage in terms of all the circuit components while minimizing the loading overhead by reducing the number of internal circuit nodes that need to be tapped. Parameter tolerances are incorporated through either statistical or mathematical analysis to determine the threshold for failure alarm.